Long-term outcomes of lupus nephritis treated with regimens based on cyclophosphamide and mycophenolate mofetil. (July 2020) - Prasad, Narayan; Kurian, Jithu; Agarwal, Vikas; Bhadauria, Dharmendra; Behera, Manas; Yacha, Monika; Kushwaha, Ravi; Agrawal, Vinita; Jain, Manoj; Gupta, Amit
Introduction: Lupus nephritis (LN) has a considerable impact on the morbidity and mortality of systemic lupus erythematosus (SLE) patients. Long-term comparative outcome data from the Indian subcontinent on treatment regimens with cyclophosphamide (CYP) and mycophenolate mofetil (MMF) are sparse. We assessed renal and patient survival for these patients in terms of the types of induction – CYP or MMF – and the two maintenance therapies – MMF or azathioprine (AZA). Methods: We retrospectively analysed outcomes of 100 LN patients, 67 treated with CYP (26 class III, 25 class IV, 6 class III + V and 10 class IV + V; 40 Euro lupus regimen and 27 National Institutes of Health regimen) and 33 treated with a MMF-based regimen with steroids between July 2008 and June 2018. Data regarding demographic, clinical and histopathological features and the treatment given to all patients were extracted. Outcomes between the two regimens CYP and MMF were compared in terms of remission, dialysis and patient survival. Results: The clinical characteristics were similar in both groups, except that the activity index was higher in CYP patients (6.13 ± 4.48 vs. 4.61 ± 2.80). However, the chronicity index was similar. The overall remission rate was 70% at the end of induction. The rates of complete remission, partial remission and non-responders in the CYP group were 46.2%, 23.9% and 29.9%, respectively. However, in the MMF group, the corresponding rates were 57.6%, 12.1% and 30.3%, respectively. The 1-, 2-, 3-, 4-, 5- and 10-year patient survival rates in the CYP group were 89.5%, 86.2%, 86.2%, 83.8%, 83.8% and 83.8%, respectively. In the MMF induction group, the corresponding rates were 93.9%, 93.9%, 89%, 89%, 89% and 89%, respectively. At the end of the study, rates of end-stage renal disease in the MMF group and CYP group were 7.5% and 12.1%, respectively. The death-censored and non-censored renal survival rates were also similar in the long term. With regard to maintenance therapy, 3/56 (5.3%) in the MMF group and 7/34 (20.5%) in the AZA group experienced doubling of serum creatinine ( p  = 0.03). Conclusions: Long-term outcomes in terms of patient and renal survival of LN patients treated with CYP and MMF induction are similar. Doubling of serum creatinine occurred more with AZA-based maintenance therapy than with MMF-based maintenance therapy. Most deaths occurred during induction, and sepsis was the most common cause of death.